Training and electrocardiographic abnormalities in the elderly. - Sidney, K H (1977)
Electrocardiograms (CM5 lead, where one lead is attached in the V5 position and one at the manubrium sterni, with the neutral lead on the back of the neck) have been recorded from 14 men and 25 women aged 60 to 75 years, at rest, during progressive bicycle ergometer exercise to 75 to 85 per cent maximum oxygen intake, and during the subsequent recovery phase. Earlier studies showing a high frequency of ischaemic electrocardiographic abnormalities in women are confirmed; it is suggested that this may reflect a high work load per unit mass of myocardium. Training induces an elevation of the ST segment at rest and during recovery, with a reduction in ST depression during work at a given heart rate, the exercise changes being related to the intensity and frequency of training selected by the subject. Possible explanations of the response to regular exercise include not only the development of the collateral circulation, but also a lessening of the hyperkalaemia of effort and a reduction in the work load per unit mass of myocardium secondary to hypertrophy or a change in the average dimensions of the heart.